2011
DOI: 10.4322/natcon.2011.007
|View full text |Cite
|
Sign up to set email alerts
|

Small-sized Fish Assemblages Do not Differ Between a Native and a Recently Established Non-indigenous Macrophyte in a Neotropical Ecosystem

Abstract: Hydrilla verticillata recently invaded a protected area in the Upper Paraná River floodplain. In a rare opportunity, when this non-indigenous species co-occurred with the native Egeria najas in a secondary channel of the river, we assessed its effects on assemblage of small-sized fish. Traps were used to catch fish inside macrophyte patches in periods of low and high water. We assessed fish abundance, biomass, diversity, richness and the community composition (using a DCA). The number of fish species did not d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 19 publications
1
16
0
Order By: Relevance
“…Previous studies have shown that several aquatic communities are not affected by invasive macrophytes if the architecture and biomass of the invasive species are similar to those of native species (Douglas & O'Connor , Aday , Cunha et al . ). Nevertheless, we hypothesize that patches with low U. arrecta biomass represent patches at which this species is at the early stages of invasion.…”
Section: Discussionmentioning
confidence: 97%
“…Previous studies have shown that several aquatic communities are not affected by invasive macrophytes if the architecture and biomass of the invasive species are similar to those of native species (Douglas & O'Connor , Aday , Cunha et al . ). Nevertheless, we hypothesize that patches with low U. arrecta biomass represent patches at which this species is at the early stages of invasion.…”
Section: Discussionmentioning
confidence: 97%
“…Some studies have failed to identify impacts from invasive species that were in low or similar abundance to native species (Dougas & Ó Connor, 2003;Aday, 2007). For example, surveys in the River Paraná showed that fish species richness was no different in the invasive hydrilla than in native Egeria najas, and this finding was attributed in part to similar biomass of both macrophytes (Cunha et al, 2011). Investigation of impacts along a gradient of invasive density is necessary to identify abundance thresholds above which impacts would occur.…”
Section: Impacts Of Invasive Speciesmentioning
confidence: 99%
“…Because of this complexity, these areas contain high diversity and abundance of small-sized fish (Delariva et al 1994;Meschiatti et al 2000;Neiff et al 2009;Dibble and Pelicice 2010;Cunha et al 2011;Gomes et al 2012) which have particular behavior patterns, such as low swimming activity and high exploitation of interstices among the roots (Priyadarshana et al 2001). The habitat provided by macrophytes is favorable for these fish owing to the high availability of food resources like algae and invertebrates (Melo et al 2002;Colon-Gaud et al 2004;Bickel and Closs 2008;Thomaz et al 2008;Murakami et al 2009;Mormul et al 2010;Colares et al 2013).…”
Section: Introductionmentioning
confidence: 96%